Preparation of Nd-Fe-B/α-Fe nanocomposite by chemical reduction method - Lim, Darryl Yu Zhi. (2009)
Nanocomposite Nd-Fe-B alloys consisting of exchange coupled soft α-Fe phase and hard Nd2Fe14B phase have attracted considerable attention due to its high (BH)max. In this project, the magnetic properties of Nd-Fe-B based nanocomposite magnet prepared by solution techniques are studied. Nd-Fe-B based alloys are prepared by using the chemical reduction method. Reduction of Fe2+ and Nd3+ ions were achieved by using BH4- ions followed by heat treatment to obtain the desire phase.